Cyber Economy Impact on the Labor Market - Michev, Georgi (Research Papers, 2020)
The continuously increasing influence of digital technology has impact in various aspects of the economy. The research focuses on the impact of digitalization and automation to the labor market. The main goal is to illustrate the effect of cyber economy and its influence on the labor market transformation. Object of the research is the labor market and subject is the cyber economy.